2013
DOI: 10.1108/14626001311298394
|View full text |Cite
|
Sign up to set email alerts
|

Small business performance: business, strategy and owner‐manager characteristics

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
274
6
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(308 citation statements)
references
References 44 publications
(110 reference statements)
15
274
6
13
Order By: Relevance
“…The significant effect of size on economic-financial performance has been widely discussed in literature [49,100,101]. However, in our case, there is no significant impact on the manager's perception of performance.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The significant effect of size on economic-financial performance has been widely discussed in literature [49,100,101]. However, in our case, there is no significant impact on the manager's perception of performance.…”
Section: Discussionmentioning
confidence: 49%
“…The age of the firm, meanwhile, has a significant impact on the manager's perception of performance, and this can provide proof of the impact of the company's life cycle (and, therefore, the experience effect) on their ability to improve organizational performance as Blackburn et al [101] have proposed. However, the fact that a firm's age has no significant effect on business performance may suggest an impact much more in the long term.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Outside of this range, the expectation is that the survival of the enterprise will be compromised either through a lack of relevant experience or a desire to retire (Andersson Joona 2010;Haapanen and Tervo 2009). It is acknowledged that the survival of the enterprise is not solely reliant on the human capital of the entrepreneur, but that they will be able to draw upon the human capital of their employees, especially as these enterprises have moved through the start-up phase. However, scholars such as Blackburn, Hart and Wainwright (2013) and Hansen and Hamilton (2011) note how the owner-managers of SMEs play an important role in determining the strategies pursued, are a key resource for small firms, and ultimately have an important influence on the performance achieved by the firm. These direct and indirect influences on survival are shown by Figure 2, with influences on both the performance of the firm and the performance threshold.…”
Section: This Comparison Is Based On the Findings Of Studies Such As mentioning
confidence: 99%
“…Most studies on success determinants distinguish between firm-internal and external factors (Storey, 1994;Schutjens and Wever, 2000;Davidsson et al, 2010;Risselada and Schutjens, 2017). Numerous academic studies have shown that it is the characteristics of firms and entrepreneurs that are the primary 'firminternal' drivers of firm success and firm growth, either as direct influences through entrepreneurial competences (Tamásy, 2006), management or strategic experience, or financial capital (Santarelli and Vivarelli, 2007), or indirect via personality factors that lead to ambitions for firm growth, which in turn is a prerequisite for firm success (Davidsson, 1991;De Tienne et al, 2008; for recent overviews, see Gilbert et al, 2006;Davidsson et al, 2010;Blackburn et al, 2013;Van Witteloostuijn et al, 2015).…”
Section: Literature Overview and Hypothesesmentioning
confidence: 99%